Critical success factors for successful implementation of enterprise resource planning systems in manufacturing organizations - Arokiasamy, Sawaridass (2004)
This study attempts to study critical success factors affecting Enterprise Resource Planning (ERP) systems implementation success in Malaysian manufacturing organization. Organizational resistance is used in order to understand the moderating effect on the above relationship. User satisfaction and predetermined goals were used to judge whether an ERP system implementation is a success or failure.